Genealogi Pendidikan Perempuan dalam Islam: Mengurai Akar Sosial-Historis - Nur Sahed (EL-TARBAWI, 2020)
In pre-Islamic times, women did not have the same rights as men including in the world of education. But in social history, in the early days of Islam women had the same right to obtain education. This research put forward a thesis, that in historical record, women have the equal educational rights. In the time of Prophet, there were discussion forums between the Prophet Muhammad and Muslim women. This equality of rights also continued in the era of classical Islam, where women also received education in the Kuttab, Madrasas, and colleges. In Indonesia, the passion for muslim women's movement in the world of education is very high, this can be seen from the many movements carried out by female leaders in the world of education to the establishment of many Islamic women's organizations in Indonesia from pre-independence to post-independence.